Tradisi Pembacaan Surat Yasin di Ponpes Panggung Tulungagung: Dampak Terhadap Nilai Sosial Kemasyarakatan dan Keagamaan - Islamiati, Indria Nuri; Musthofa, Chabib (CV Omah Kreator, 2024)
The Holy Quran is a sacred scripture that plays a vital role in the lives of Muslims. Surah Yasin is one of the chapters that holds exceptional significance and benefits in daily life. The tradition of reciting Surah Yasin at Pondok Pesantren Panggung Tulungagung has become an integral part of the daily lives of students and the surrounding community. This study aims to explore the impact of the Surah Yasin recitation tradition on social and religious values in the Pondok Pesantren Panggung Tulungagung environment. This study employs a qualitative method with a descriptive approach. Data is collected through in-depth interviews, participatory observation, and documentation.The results of the research show that the tradition of reading Surah Yasin has a positive impact on social and religious values ​​in the Panggung Tulungagung Islamic Boarding School environment. This tradition strengthens social ties between students and the community, increases religious values, and deepens understanding of religion. Apart from that, this tradition also has a positive impact on the surrounding community, such as strengthening relationships, fostering a sense of caring, and increasing spirituality.